My Top Five Concepts for Selecting Lower Extremity Exercises For Cruciate Ligament and Patellofemoral Rehabilitation - Rafael F Escamilla (International Journal of Sports Physical Therapy)
This clinical commentary will address five key concepts that can be used by clinicians as criteria for selecting lower extremity weight bearing exercises (WBE) and non-weight bearing exercises (NWBE) employed for cruciate ligament and patellofemoral rehabilitation. The following will be discussed for both cruciate ligament and patellofemoral rehabilitation: 1) Knee loading varies between WBE and NWBE; 2) Knee loading varies with technique variations within WBE and NWBE; 3) Knee loading varies between different WBE; 4) Knee loading varies as a function of knee angle; and 5) Knee loading increases with increased knee anterior translation beyond toes.